PRACTICE OF USING MANUFACTURING OUTSOURCING AND POSSIBLE SUPPLY CHAINS TRANSFORMATION IN THE FASHION INDUSTRY - N. Yu. Barkova (Вестник университета)
The structure of supply chains in the fashion industry has been considered, their main participants have been highlighted. The pros and cons of international production outsourcing for companies working in this industry also have been reviewed. The main factors that are prerequisites for possible changes in the configuration of global supply chains in the fashion industry have been designated. The impact of digital technologies on the configuration of supply chains has been evaluated. The functioning of the «fast «digital factories of Adidas «Speedfactory» and «Faberlic» company has been analysed, which use digital technologies in the production process of manufacturing goods in the fashion industry and are aimed at the maximum reduction of the inventory fulfillment cycle in the fashion industry.